2016
DOI: 10.1002/mrm.26193
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and permittivity maps of brain tissues derived from water content based on T1‐weighted acquisition

Abstract: Human brain and phantom EP images suggest that water content is a dominating factor in determining the electrical properties of tissues. Despite possible literature inaccuracies, the proposed method offers EP maps that can provide complementary information to current approaches, to facilitate EPT scans in clinical applications. Magn Reson Med 77:1094-1103, 2017. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 76 publications
(115 reference statements)
4
99
0
Order By: Relevance
“…For the clinical purpose of tumor malignancy diagnosis, conductivity tends to provide more valuable information than permittivity in the frequency above 100 MHz because permittivity is dominated by water content, whereas conductivity is related to both water content and ion concentration (1,46,47). In the current study, a lower relative difference of permittivity than that of conductivity has been observed in the imaging experiment and confirmed by dielectric measurement with a probe.…”
Section: Discussionsupporting
confidence: 70%
“…For the clinical purpose of tumor malignancy diagnosis, conductivity tends to provide more valuable information than permittivity in the frequency above 100 MHz because permittivity is dominated by water content, whereas conductivity is related to both water content and ion concentration (1,46,47). In the current study, a lower relative difference of permittivity than that of conductivity has been observed in the imaging experiment and confirmed by dielectric measurement with a probe.…”
Section: Discussionsupporting
confidence: 70%
“…This overestimated derived brain conductivity suggests that the agarose gel might not be an accurate model for brain conductivity. To build an appropriate brain conductivity surrogate, in addition to ion concentrations (Na + , K + , CL − ), factors such as ion binding effects, 42 the mobility of conductive ions, 43,44 and tissue water fraction 17,40 should be considered in future studies. Recently, van Lier et al 18 demonstrated a positive correlation between brain conductivity and sodium concentration at 7T, and the regression slope and offset was found to be in accordance with saline solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as cellular membranes presented extremely low resistance to the electromagnetic (EM) wave propagation at RF and microwave frequencies, tissue conductivity becomes highly correlated with the tissue water fraction. Based on this correlation model, conductivity maps were computed from the water content maps of the brain …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a biological point of view, the human brain is a multilayered heterogeneous structure with different relative permittivities ε r . Michel, Hernandez, and Lee () provide specific values for brain mediums and demonstrate that water concentration levels result in different permittivities. Indeed, the electrical characteristics of the water molecule and, consequently, the relative permittivity of the medium are function of the wave frequency.…”
Section: Existing Tracking Systemsmentioning
confidence: 99%